2020
DOI: 10.1103/physrevb.101.014514
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced suppression of charge density wave and emergence of superconductivity in 1TVSe2

Abstract: We report pressure evolution of charge density wave (CDW) order and emergence of superconductivity (SC) in 1T-VSe2 single crystal by studying resistance and magnetoresistance behavior under high pressure. With increasing quasi-hydrostatic pressure the CDW order enhances with increase of the ordering temperature up to 240K at 12 GPa. Upon further increase of pressure, the resistance anomaly due to CDW order gets suppressed drastically and superconductivity emerges at ∼15 GPa, with the onset critical temperature… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 41 publications
9
31
0
Order By: Relevance
“…The layers are linked with weak van der Waals forces allowing various creative materials-design possibilities, such as the intercalation of foreign atoms and molecules 13 , exfoliation of the sample to the desired number of layers 14,15 , as well as applications in electronic devices 16,17 . Intriguingly, recent studies of VSe 2 revealed dramatic changes in the CDW and new physical properties such as a pseudo-gap, Fermi arc, and emergent superconductivity [18][19][20][21] ; naturally, this motivates us to investigate the behavior of this material under high pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The layers are linked with weak van der Waals forces allowing various creative materials-design possibilities, such as the intercalation of foreign atoms and molecules 13 , exfoliation of the sample to the desired number of layers 14,15 , as well as applications in electronic devices 16,17 . Intriguingly, recent studies of VSe 2 revealed dramatic changes in the CDW and new physical properties such as a pseudo-gap, Fermi arc, and emergent superconductivity [18][19][20][21] ; naturally, this motivates us to investigate the behavior of this material under high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 4, we plot the temperature-pressure dependent structural change from trigonal ̅ to monoclinic together with the CDW and superconductivity results from Ref. 21.…”
Section: Introductionmentioning
confidence: 99%
“…[ 32 ] VSe 2 nanosheets grown on mica substrates via a single‐step chemical vapor deposition showed the excellent metallic feature with conductivity of up to 10 6 S m −1 , which is 1–4 orders of magnitude greater than that of several conductive 2D materials. [ 38 ] 1T‐VSe 2 single crystals, with increasing quasi‐hydrostatic pressure up to 12 GPa CDW order enhances up to temperature of 240 K, but further increment in pressure(until 15 GPa) suppresses CDW ordering and emergence of superconductivity come into picture at a critical temperature of 4 K. [ 107 ] Resistivity measurements with a six‐terminal Hall bar devices showed increase in electrical resistivity with increase in temperature, indicating the metallic behavior of the VSe 2 nanosheets. Similarly, VTe 2 nanosheets show the metallic nature with electrical conductivity of 1.7 × 10 6 S m −1 at room temperature and is comparable with other metallic 2D materials.…”
Section: Structure and Properties Of Vx2mentioning
confidence: 99%
“…As for the transport properties of 1T-VSe 2 under pressure, controversial results have been reported. Specifically, Sahoo et al reported that the CDW transition temperature (T CDW ) first increases marginally up to 5 GPa and then increases rapidly, and accompanying by nonhydrostatic pressure-induced suppression of CDW, superconductivity emerges at ∼15 GPa (Sahoo et al, 2020). However, soon after, Feng et al found that the CDW transition temperature was enhanced linearly by increasing pressure, reaching 358 K at 14.6 GPa and no superconducting transition is observed under quasi-hydrostatic pressure up to 29.6 GPa (Feng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, the detailed properties of 1T-VSe 2 under pressure remain far from being well explored. In addition, in these reports, the pressures applied in the XRD, Raman, and resistance measurements are below 30-35 GPa (Friend et al, 1978;Sereika et al, 2020;Feng et al, 2020;Sahoo et al, 2020). For pressures above 35 GPa, the evolution of structural and transport properties are still unclear.…”
Section: Introductionmentioning
confidence: 99%